Navigating Mental Health Challenges in Conflict Zones: A Mixed Method Literature Review - Nisa, Zia-un; Talat, Afsheen; Ellahi Khan, Shaheer; Elahi, Aqsa; Ghazanfar, Iqra (Pakistan Journal of Humanities and Social Sciences, 2024)
According to the World Mental Health Report (2022), 22% of the population living in conflict-afflicted areas have mental health disorders, including anxiety, depression, and Post-Traumatic Stress Disorder (PTSD). Mental health disorders are one of the most serious and underrepresented effects of surviving in conflict-afflicted areas. To investigate the prevalence of mental health disorders and potential risk factors that impact individuals residing in conflict regions and explore their lived experiences. A mixed-method literature review of the studies was conducted between January 2015 to August 2024. It combined substantial evidence from 15 quantitative (n=8) and qualitative (n=6) studies that were exposed to large-scale conflicts in the past ten years. The data was gathered through a range of databases (Google Scholar, Scopus, PubMed, PsycINFO. Initially, 187 studies were identified, and 51 remained after screening. In total, 15 studies met the inclusion and exclusion criteria. The results suggested that individuals in conflicted areas have a high prevalence of severe mental health disorders like PTSD, anxiety, and depression. Moreover, some risk factors that contributed were persistent exposure to violence, loss of livelihood, and displacement. Consequently, religious and psychosocial coping mechanisms did provide some relief. However, these mechanisms dominated the treatment-seeking decisions and prevented individuals from opting for biomedical healthcare practices. Conclusion: This review highlighted the need for a multidisciplinary approach to curb these areas' growing mental health imbalance. In addition to being a humanitarian right and necessity, providing adequate mental health facilities is a vital component of rebuilding and recovering the affected communities.